Fourier Transform Infrared Spectroscopy - Upadhyay, Manan (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTFT-IR stands for Fourier Transform Infrared, the preferred method of infrared spectroscopy. The resulting spectrum represents the molecular absorption and transmission, creating a molecular fingerprint of the sample. Like a fingerprint no two unique molecular structures produce the same infrared spectrum. This makes infrared spectroscopy useful for several types of analysis.FT-IR CAN provide;• It can identify unknown materials• It can determine the quality or consistency of a sample• It can determine the amount of components in a mixture